2011
DOI: 10.1371/journal.pone.0027649
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide That Binds Specifically to the β-Amyloid of Alzheimer's Disease: Selection and Assessment of Anti-β-Amyloid Neurotoxic Effects

Abstract: The accumulation of the amyloid-β peptide (Aβ) into amyloid plaques, an essential event in Alzheimer's disease (AD) pathogenesis, has caused researchers to seek compounds that physiologically bind Aβ and modulate its aggregation and neurotoxicity. In order to develop new Aβ-specific peptides for AD, a randomized 12-mer peptide library with Aβ1-10 as the target was used to identify peptides in the present study. After three rounds of selection, specific phages were screened, and their binding affinities to Aβ1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Aβ1-42 stock solution (100 µM) was prepared by dissolving the peptide fragment powder (two different lots from Sigma-Aldrich were used, namely lot n. 079K8729 and SLBC5079V) in sterile Milli-Q water, as previously reported [43], [58], [60][65]. Aliquots (5 µl) were lyophilized and stored at −20°C until use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ1-42 stock solution (100 µM) was prepared by dissolving the peptide fragment powder (two different lots from Sigma-Aldrich were used, namely lot n. 079K8729 and SLBC5079V) in sterile Milli-Q water, as previously reported [43], [58], [60][65]. Aliquots (5 µl) were lyophilized and stored at −20°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the inhibitory activity of small molecules (small peptides included) able to break down the structural organization of soluble or aggregating Aβ1-42 in the fibrillogenesis process is under investigation [57], [58] with the aim of identifying novel inhibitors of Aβ1-42 aggregation and toxicity, a major topic in AD research [59]. In this context, we considered the direct effects of carnosine, a naturally occurring dipeptide in nervous cells, on the fibrillogenesis process of the Aβ1-42 fragment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that several alternative approaches have preventative effects on the progression of AD, including anti-Aβ antibodies, inhibitors of β- and γ-secretases, antioxidants and anti-inflammatory agents 9 12 . However, the stability, validity, cost, safety and development time restrict the use of these treatments for preventing AD 13 . Thus, searching for a safer and more effective drug for the treatment of AD remains an important challenge in drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they also exhibit accelerated metabolism in the body. Their limitations include instability on the tumor cell surface and alterations according to the environment [ 17 , 18 ]. Sugahara et al found a handful of peptides that could specifically interact with the tumor cell surface, constituting ideal carriers of targeted therapy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%